LAYANAN M-BANKING DAN PENGARUHNYA PADA KEPUASAN DAN LOYALITAS: STUDI EMPIRIS BANK BNI - Livia Hening Pratiwi; Jeanne Ellyawati (Modus, 2023)
Amidst the rapid advancement of digital technology, mobile banking (M-Banking) is the most viable solution within the banking industry, particularly for financial institutions characterized by extensive operational territories, which are otherwise hindered by the limited availability of physical service branches. This study examines the effect of M-Banking service quality on customer satisfaction and loyalty in using Bank BNI's M-Banking facilities. By integrating service quality theory (SERVQUAL), technology acceptance model (TAM), and attitude theory, this study examines the effect of perceived M-Banking service quality on customer satisfaction and loyalty. The quality of M-Banking services is measured through security assurance, convenience, efficiency, ease of use, reliability, and responsiveness. Data was collected through a cross-sectional survey using a closed questionnaire of 200 respondents. The sampling method was determined by purposive and snowball sampling. Hypothesis verification was carried out using regression analysis. The study results show that the quality of M-Banking services positively affects customer satisfaction, except for efficiency variable, which is not proven to affect satisfaction. Furthermore, satisfaction has a positive effect on customer loyalty. The study findings show that the better the quality of M- Banking services, the more customer satisfaction will increase, increasing customer loyalty. Keywords:       security assurance; convenience; efficiency; ease of use; reliability and responsiveness Di tengah pesatnya kemajuan teknologi digital, penggunaan mobile banking (M-Banking) menjadi solusi terbaik dalam industri perbankan, terutama bagi bank yang memiliki wilayah operasional yang luas namun terkendala dengan terbatasnya jumlah kantor layanan fisik yang tersedia. Penelitian ini bertujuan untuk menguji pengaruh kualitas layanan M-Banking pada kepuasan dan loyalitas nasabah dalam menggunakan fasilitas M-Banking bank BNI. Dengan mengintegrasikan teori kualitas layanan (SERVQUAL), technology acceptance model (TAM) dan teori sikap, penelitian ini menguji pengaruh persepsi kualitas layanan M-Banking pada kepuasan dan loyalitas nasabah. Kualitas layanan M-Banking diukur melalui jaminan keamanan, kenyamanan, efisiensi, kemudahan penggunaan serta keandalan dan daya tanggap. Data dikumpulkan melalui desain cross-sectional survey menggunakan kuesioner tertutup pada 200 responden. Metode pengambilan sampel ditentukan dengan purposive dan snowball sampling. Verifikasi hipotesis dilakukan dengan menggunakan analisis regresi. Hasil studi menunjukkan bahwa kualitas layanan M-Banking berpengaruh positif pada kepuasan nasabah, kecuali variabel efisiensi yang tidak terbukti memengaruhi kepuasan. Selanjutnya, kepuasan berpengaruh positif pada loyalitas nasabah. Temuan studi menunjukkan bahwa semakin baik kualitas layanan M-Banking, maka akan semakin meningkatkan kepuasan nasabah dan selanjutnya mengarah pada peningkatan loyalitas nasabah. Kata kunci: jaminan keamanan; kenyamanan; efisiensi; kemudahan penggunaan; keandalan dan daya tanggap.